Mechanism of Rotenone Toxicity against Plutella xylostella: New Perspective from a Spatial Metabolomics and Lipidomics Study - Li, Ping; Tian, Yongqing; Du, Mingyi; Xie, Qingrong; Chen, Yingying; Ma, Lianlian; Huang, Yudi; Yin, Zhibin; Xu, Hanhong; Wu, Xinzhou (Journal of agricultural and food chemistry, 2023)
The botanical pesticide rotenone can effectively control target pest Plutella xylostella, yet insights into in situ metabolic regulation of P. xylostella toward rotenone remain limited. Herein, we demonstrated metabolic expression levels and spatial distribution of rotenone-treated P. xylostella using spatial metabolomics and lipidomics. Specifically, rotenone significantly affected purine and amino acid metabolisms, indicating that adenosine monophosphate and inosine were distributed in the whole body of P. xylostella with elevated levels, while guanosine 5′-monophosphate and tryptophan were significantly downregulated. Spatial lipidomics results indicated that rotenone may significantly destroy glycerophospholipids in cell membranes of P. xylostella, inhibit fatty acid biosynthesis, and consume diacylglycerol to enhance fat oxidation. These findings revealed that high toxicity of rotenone toward P. xylostella may be ascribed to negative effects on energy production and amino acid synthesis and damage to cell membranes, providing guidelines for the toxicity mechanism of rotenone on target pests and rational development of botanical pesticide candidates.